Effective breastfeeding techniques and associated factors among lactating women: a community-based study, north east Ethiopia - Mislu, Esuyawkal; Kumsa, Henok; Arage, Mulugeta Wodaje; Shitie, Anguach; Adimasu, Abebe (Frontiers in Public Health, 2024)
Background: Effective breastfeeding techniques, which include proper attachment, positioning, and suckling, offer a range of benefits for both the mother and the infant. These techniques ensure efficient milk transfer, reduce the risk of infections, support optimal infant weight gain, enhance maternal comfort, and foster a strong emotional bond. This study aimed to identify the magnitude and factors associated with effective breastfeeding techniques among lactating women in the Legambo district of South Wollo, Ethiopia in 2022.Method: A community-based cross-sectional study was conducted from September to November 2022. Samples were selected using a multi-stage sampling method from eighteen wards (kebele).Data were collected using an interviewer-administered structured questionnaire and an observational checklist. The collected data were entered into Epi-Data and then exported to SPSS version 25.0 for analysis. Descriptive statistics and bivariate and multivariable logistic regression analyses were performed to identify the magnitude and associated factors. Variables with a p-value less than 0.05 on multivariable analysis were considered as independent factors associated with the outcome variable.Results: Six hundred ten lactating women were included for observation and interviewed, resulting in a 96.2% response rate. The magnitude of effective breastfeeding technique practice was found to be 25.9% (95% CI: 22.47%-29.57%). Factors associated with effective breastfeeding technique practice included being a working woman (AOR=1.70; 95%CI: 1.07-2.72), age between 26 and 30 (AOR=0.37; 95%CI: 0.16-0.84), urban residence (AOR=1.59; 95%CI: 1.06-2.39), initiating breastfeeding one to two hours after birth (AOR=0.27; 95%CI: 0.16-0.43), and initiating breastfeeding after two hours of birth (AOR=0.34; 95%CI: 0.17-0.67). Additionally, not receiving breastfeeding education (AOR=0.46; 95%CI: 0.30-0.72) and experiencing current breast problems (AOR=0.28; 95%CI: 0.28-0.75) were also found to have a significant association with effective breastfeeding technique practice.Only one in four women demonstrated effective breastfeeding techniques, indicating that their practice was below the WHO's recommendations. Therefore, it is crucial to consider the identified variables in order to improve the practice of effective breastfeeding techniques.